Case studies in system of systems, enterprise systems, and complex systems engineering - Gorod, Alex; White, Brian E.; Ireland, Vernon; Gandhi, S. Jimmy; Sauser, Brian (Complex and enterprise systems engineering series, 2015)
Suitable as a reference for industry practitioners and as a textbook for classroom use, Case Studies in System of Systems, Enterprise Systems, and Complex Systems Engineering provides a clear understanding of the principles and practice of system of systems engineering (SoSE), enterprise systems engineering (ESE), and complex systems engineering (CSE). Multiple domain practitioners present and analyze case studies from a range of applications that demonstrate underlying principles and best practices of transdisciplinary systems engineering.